Biomechanical factors affecting running economy - Kyröläinen, H.; Belli, A.; Komi, P. V. (Medicine & Science in Sports & Exercise, 2001)
Purpose: The present study was designed to investigate kinematics, kinetics, and muscle activity for explaining running economy at different running speeds. Methods: A total of 17 young endurance runners ran at 12-13 different running speeds. Respiratory gases were collected. Kinematic records were obtained by a high-speed video camera, and 3-D ground reaction forces (GRF) were measured simultaneously with telemetric EMG recordings of the selected leg muscles. In the analysis, joint moments and power were calculated by inverse dynamic methods. Results: The oxygen consumption and energy expenditure increased quite linearly with increasing running speed. However, already at the slowest speed, interindividual differences in running economy were noticed, and they increased with increasing running speed. Simultaneously, the instantaneous joint moment-angular velocity curves of the ankle and knee joints shifted to the right and upward, thus increasing joint power in the push-off phase of contact. Most definitive was the increase in EMG-activity of the BF muscle and its correlation with energy expenditure (r = 0.48, P < 0.05). This two-joint muscle seems to be very active during the maximal running: its amplitude increased (P < 0.05) both in the swinging and contact phases with increasing running speed. Conclusions: The increased EMG of working muscles and the associated increase in power output may partly explain the increased energy expenditure with increasing running speed. Lower performances in running economy by some of the athletes may also be explained by poor running technique, such as unusually high braking and mediolateral forces, which may be caused by limited action of the hamstring muscles. However, no exclusive biomechanical parameters could be identified to explain the running economy.